2017
DOI: 10.1007/s00572-016-0759-3
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungus responses to disturbance are context-dependent

Abstract: Anthropogenic disturbance is one of the most important forces shaping soil ecosystems. While organisms that live in the soil, such as arbuscular mycorrhizal (AM) fungi, are sensitive to disturbance, their response is not always predictable. Given the range of disturbance types and differences among AM fungi in their growth strategies, the unpredictability of the responses of AM fungi to disturbance is not surprising. We investigated the role of disturbance type (i.e., soil disruption, agriculture, host perturb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 83 publications
4
41
2
Order By: Relevance
“…For instance, uncultured taxon Glomus VT166 was an indicator species of undisturbed habitats in our study; previous studies have shown the same to be characteristic of intact habitats (Moora et al., ) and Tibetan alpine meadows (Y. Liu, personal observation). By contrast, Paraglomus VT281 (cultured, related to Paraglomus laccatum ) was an indicator of anthropogenic wooded habitats in this study; it has previously been found to be associated with managed grasslands (Ciccolini et al., ) and other heavily disturbed ecosystems (Van Der Heyde et al., ). Generally, the high number of recorded indicator species shows that a relatively high proportion of taxa favoured either natural or anthropogenic plots.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…For instance, uncultured taxon Glomus VT166 was an indicator species of undisturbed habitats in our study; previous studies have shown the same to be characteristic of intact habitats (Moora et al., ) and Tibetan alpine meadows (Y. Liu, personal observation). By contrast, Paraglomus VT281 (cultured, related to Paraglomus laccatum ) was an indicator of anthropogenic wooded habitats in this study; it has previously been found to be associated with managed grasslands (Ciccolini et al., ) and other heavily disturbed ecosystems (Van Der Heyde et al., ). Generally, the high number of recorded indicator species shows that a relatively high proportion of taxa favoured either natural or anthropogenic plots.…”
Section: Discussioncontrasting
confidence: 75%
“…The use of cultured status as a proxy for function in AM fungi has, however, been challenged based on observed responses to logging in boreal forests (Hart, Zaitsoff, Van Der Heyde, & Pither, ). In addition, Van Der Heyde, Ohsowski, Abbott, and Hart () also showed that AM fungal responses to disturbance are context‐dependent, depending on disturbance type, and might be phylogenetically conserved at family or higher taxonomic levels. Broadly speaking, little information exists concerning AM fungal traits, despite considerable theoretical interest.…”
Section: Discussionmentioning
confidence: 99%
“…First, AMF are common in tropical forests (Marinho, da Silva, Oehl, & Maia, ), while ectomycorrhizal fungi are colonizing shrubs and trees in temperate montane forests (Finlay, ). AMF are part of a neglected component of neotropical biodiversity, which associations with other elements of the biota, such as the vegetation and their response to human intervention have been little studied (Van der Heyde, Ohsowski, Abbott, & Hart, ), and the few studies available reveal conflicting results. In tropical forests, some studies have shown that, in the short term, the AMF species diversity is not affected by the slash and burn (Aguilar‐Fernández, Jaramillo, Varela‐Fregoso, & Gavito, ); whereas other studies disclose that AMF species tend to decrease, with increased levels of disturbance (Sheldrake et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The relative dominance of members of the order Glomerales and the higher sensitivity of the large spored species of AM fungi in forest soils of Delhi might be because of their trade-off in resource allocation either by many small or fewer large spores, with each having a similar colonisation capacity (Brundrett & Ashwath, 2013). It may also be a part of a life-history strategy for the different AM families (Varela-Cervero, López-García, Barea, & Azcón-Aguilar, 2016;van der Heyde et al, 2017). Inclusion of the biovolume parameter in the analysis suggested that the AM fungi that produce larger spores produce them in smaller numbers suggesting resource allocation optimisation.…”
Section: Discussionmentioning
confidence: 99%
“…High population density and the ensuing overuse of scarce resources have put heavy pressure on the soil environment in Delhi, India. Since arbuscular mycorrhizal (AM) fungi are the organisms that live in the soil, they are sensitive to factors that cause soil disturbance and their response is not always predictable (van der Heyde, Ohsowski, Abbott, & Hart, 2017). Different species of AM fungi have been shown to be differntially sensitive to different agricultural practices (Oehl, Sieverding, Ineichen, Ris, & Boller, 2005, Tchabi, Hountondji, Laouwin, Coyne, & Oehl, 2009), heavy metal pollution, elevated CO 2 concentration and climate warming (Drigo et al2010, Dumbrell et al2011.…”
mentioning
confidence: 99%